2017
DOI: 10.7150/jca.20409
|View full text |Cite
|
Sign up to set email alerts
|

Updated Nomogram Incorporating Percentage of Positive Cores to Predict Probability of Lymph Node Invasion in Prostate Cancer Patients Undergoing Sentinel Lymph Node Dissection

Abstract: Objectives: To update the first sentinel nomogram predicting the presence of lymph node invasion (LNI) in prostate cancer patients undergoing sentinel lymph node dissection (sPLND), taking into account the percentage of positive cores.Patients and Methods: Analysis included 1,870 prostate cancer patients who underwent radioisotope-guided sPLND and retropubic radical prostatectomy. Prostate-specific antigen (PSA), clinical T category, primary and secondary biopsy Gleason grade, and percentage of positive cores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

6
4

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…5 A high sensitivity for identification of LN metastases could be demonstrated for this radioisotopeguided sentinel procedure in PCa. [6][7][8][9] Nevertheless, the pros of the current SLN detection procedure also come with some serious cons. The dependence on radioisotopes limits the application of this procedure to small parts of the developed world, and it imposes restrictions on patient planning and hospital logistics.…”
Section: Introductionmentioning
confidence: 99%
“…5 A high sensitivity for identification of LN metastases could be demonstrated for this radioisotopeguided sentinel procedure in PCa. [6][7][8][9] Nevertheless, the pros of the current SLN detection procedure also come with some serious cons. The dependence on radioisotopes limits the application of this procedure to small parts of the developed world, and it imposes restrictions on patient planning and hospital logistics.…”
Section: Introductionmentioning
confidence: 99%
“…The findings demonstrated that the diagnostic reliability of eLND and sLND were almost comparable. In sentinel cohorts, targeted sLND detected a higher rate of LN-positive patients than were expected from established nomograms [5][6][7].…”
Section: Introductionmentioning
confidence: 74%
“…The findings revealed that the diagnostic accuracies of eLND and targeted sLND were almost the same. Moreover, it was demonstrated that sLND yielded higher LN invasion (LNI) rates in sentinel cohorts than were expected from established nomograms [5][6][7].…”
Section: Introductionmentioning
confidence: 99%